Fabrication of Stewart platform actuated by pneumatic artificial muscle for foot-ankle rehabilitation - Krishnan, Subramaniam (2019)
Foot/Ankle injuries are amongst the most common injuries of the lower limb and almost 25,000 people are experiencing ankle injuries each day due to vigorous activities. Traditionally, ankle injuries are rehabilitated via physiotherapy, using simple equipment like elastic bands and rollers, requiring intensive efforts of therapists and patients. Currently, Stewart Platform rehabilitation devices are actuated by various methods including double acting pneumatic cylinder, hydraulic, electric motor and shape memory alloy is being used. The limitation of using these actuation methods is it, provides lower range of motions and required higher maintenances. The objective of this research is to fabricate Stewart Platform using Pneumatic Artificial Muscle, to analyse the range of motion of the foot/ankle, and to comparative study of the experiment and theoretical data. In this research study Stewart Platform with upper platform diameter 150 mm actuated by various diameters of Pneumatic Artificial Muscle (PAM) using air compressor is presented. The diameters of PAM used are 8 mm, 10 mm and 12 mm. Stewart Platform actuated by PAM with the diameter of 12 mm produced maximum platform angle of 31.73°, whereas PAM with the diameter of 10 mm and 8 mm produced maximum platform angle of 28.62° and 25.31° respectively. The developed Stewart Platform produced 31.73° range of motion (ROM) as comparing to the other researcher findings with a limited of ROM up to 20°. Performance of the prototype through experimental and theoretical results has proven relevant. This shows an improvement of the current work with the previous work.